HARDNESS TEST ON AL-Cu CASTING RESULTS DIE CASTING METHOD WITH VARIATION IN POUR TEMPERATURE AND PRESSURE - Akhmad Taufik; Ma'ruf Ma'ruf (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
In the automotive industry, the component parts and engine elements mostly use aluminum alloys with the casting process, one of which is aluminum with copper (Al-Cu) aluminum alloys. Metal casting die casting method is part of pressurized casting, where the metal is pressed into the mold. Many aluminum casting industries, especially small and medium industries, in the manufacture of products or components use recycled materials by the casting foundry method, so that they will affect the decrease in material properties. The die casting method is expected to be able to improve its physical and mechanical properties. The casting process using the die casting method is carried out at pour temperature (650â°C, 670â°C, and 690â°C) with variations in pressure 0 (no pressure), 2.5 MPa, 5 MPa and 7.5 MPa. The results of the hardness test showed that the pouring temperature was 650â°C and 7.5 MPa pressure was the highest hardness with a value of 72 HB and the lowest hardness value was at a temperature of 690â°C without pressure with a hardness value of 58 HB. From this study it can be concluded that the pouring temperature and pressure are very influential on the value of hardness in the casting process by die casting method.